2010
DOI: 10.1242/dev.043224
|View full text |Cite
|
Sign up to set email alerts
|

The cytolinker Pigs is a direct target and a negative regulator of Notch signalling

Abstract: SUMMARYGas2-like proteins harbour putative binding sites for both the actin and the microtubule cytoskeleton and could thus mediate crosstalk between these cytoskeletal systems. Family members are highly conserved in all metazoans but their in vivo role is not clear. The sole Drosophila Gas2-like gene, CG3973 (pigs), was recently identified as a transcriptional target of Notch signalling and might therefore link cell fate decisions through Notch activation directly to morphogenetic changes. We have generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 45 publications
4
34
0
1
Order By: Relevance
“…We had previously observed that full-length Pigs colocalised with both MTs along their length and with some actin structures when it was expressed in the ovary in vivo (Pines et al, 2010). Here, we confirmed that at elevated expression levels in the germline of the ovary, in addition to plus-end tracking, GFPPigsFL also colocalised with both the actin-rich ring canals that connect nurse cells (Fig.…”
Section: Pigs Can Bind Mts and Actin Filaments In Cultured Cells And supporting
confidence: 84%
See 4 more Smart Citations
“…We had previously observed that full-length Pigs colocalised with both MTs along their length and with some actin structures when it was expressed in the ovary in vivo (Pines et al, 2010). Here, we confirmed that at elevated expression levels in the germline of the ovary, in addition to plus-end tracking, GFPPigsFL also colocalised with both the actin-rich ring canals that connect nurse cells (Fig.…”
Section: Pigs Can Bind Mts and Actin Filaments In Cultured Cells And supporting
confidence: 84%
“…Shot has many well-identified roles from embryogenesis into adulthood, as well as during oocyte specification (Gregory and Brown, 1998;Lee et al, 2000;Röper et al, 2002;Röper and Brown, 2003). pigs 1 mutants are viable but infertile (Pines et al, 2010). Both Shot and Pigs show a ubiquitous expression pattern, although Pigs appears to be expressed only at low levels in many tissues (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations